VRCHIVE: experiences conducting an online workshop teaching intergenerational participants to create virtual reality films about their lives during the COVID pandemic. Issue 7 (3rd July 2022) - Appel, Lora; Lewis, Samantha; Kisonas, Erika; Recknagel, Jennifer
ABSTRACT: The VRCHIVE workshop was a first-of-its-kind exploratory pilot initiative to examine the feasibility of running a remote, intergenerational Virtual Reality (VR) storytelling workshop through the Toronto Public Library. The workshop took place during the COVID-19 pandemic, which has highlighted a need to develop solutions to address the digital divide and consequent increased social isolation in older adults. The overall program goals were threefold: (1) to create a 'VRCHIVE' of 360° VR films that documented participants' lives during the COVID-19 pandemic, (2) to explore the challenges and successes of the program in order to evaluate its effectiveness, and (3) to understand, broadly, the program's impact on technology literacy, feelings of isolation, and familial relationship strengthening. Five pairs of grandparents and grandchildren (n = 10) engaged in four, one-hour long online sessions each week in November 2020. Feedback was collected through facilitator observations and weekly debriefing sessions (n = 4), as well as online participant surveys (n = 3) and phone interviews (n = 2) conducted upon program completion. All intergenerational pairs successfully completed a VR film. Post-workshop, participants reported feeling less isolated, more connected with other people, and more confident in learning to use innovative technology. A detailed description of the workshop is provided, along with a discussion on recommendations for future iterations of the program that may serve as a model for other locations that wish to implement similar programming. Overall, participants reported positive experiences, and there is an appetite to sustain and scale the program in the future.